1990
DOI: 10.1002/bip.360300903
|View full text |Cite
|
Sign up to set email alerts
|

Counterion effects on the physical properties and the A to B transition of calf‐thymus DNA films

Abstract: We report measurements of the water content and swelling of wet-spun films of Na-, K-, Rb-, and Cs-DNA as a function of relative humidity (rh). The water contents (number of water molecules per base pair of DNA) of these films are found to be quite similar, indicating that the identity of the counterion species is unimportant for the water content. Since the A to B transition for these DNAs occurs at different rhs, the corresponding water contents of the A to B transition are found to be quite different. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 43 publications
4
31
0
Order By: Relevance
“…For concentrations above 1 mg/ml the volume fraction starts to decrease, indicating that interference or overlap is occurring between neighboring DNA molecules; the distance between DNA could be different at higher concentrations. This measurement of the hydration layer thickness matches well with experiments and simulations reporting that DNA affects the surrounding water from 15 to 20 Å [40][41]. The influence of a biomolecule on the surrounding water environment is much greater with DNA than with nucleotides [14] where the influence only extends to four layers.…”
Section: Thickness Of the Hydration Layersupporting
confidence: 83%
See 1 more Smart Citation
“…For concentrations above 1 mg/ml the volume fraction starts to decrease, indicating that interference or overlap is occurring between neighboring DNA molecules; the distance between DNA could be different at higher concentrations. This measurement of the hydration layer thickness matches well with experiments and simulations reporting that DNA affects the surrounding water from 15 to 20 Å [40][41]. The influence of a biomolecule on the surrounding water environment is much greater with DNA than with nucleotides [14] where the influence only extends to four layers.…”
Section: Thickness Of the Hydration Layersupporting
confidence: 83%
“…The influence of a biomolecule on the surrounding water environment is much greater with DNA than with nucleotides [14] where the influence only extends to four layers. This is reasonable because the phosphate backbone and sugar ring in DNA are highly charged and have a higher affinity for water than the exposed bases of the nucleotides [41]. This is also reflected in the fact that DNA is a stronger acid than the nucleotides.…”
Section: Thickness Of the Hydration Layermentioning
confidence: 98%
“…These studies highlighted the role of specific DNA hydration patterns and of the DNA interaction with counter-ions. In DNA aggregates, experimental evidence suggested that the transition is also affected by inter-molecular interactions (34). It is, therefore, important to understand how the change in the structural parameters of DNA upon the transition (shown in Table 1) affects the energy of intermolecular electrostatic interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Completely disordered water gives P water (q) § 0. At a typical concentration [Ϸ10 water molecules͞ phosphate (34)], ordered water in a dense DNA aggregate is likely to be close to the full dielectric saturation. If the only source of the order is water polarization around phosphates and counter-ions, the values of q, which contribute significantly to P(q), are q ϳ 2͞l, where l ϳ 3 Å is the characteristic distance between water molecules, i.e., q ϳ 2 Å Ϫ1 Ͼ Ͼ g (see Table 1).…”
Section: [5]mentioning
confidence: 99%
“…DNA hydration has been extensively studied by several gravimetric, spectroscopic, osmotic stress, calorimetric, and scattering methods. [14][15][16][17][18][19][20][21][22][23][24] However, to our knowledge, simultaneous free energy and enthalpy data have not been reported previously.…”
Section: Discussionmentioning
confidence: 99%